THE CONCEPT OF DIGITAL LAW AND THE HISTORY OF ITS DEVELOPMENT - Olim Xusanbayev (Scholar Express Journals, 2024)
This article analyses the concept of digital law and its formation, in particular, the opinions and ideas of various legal scholars about digital law, as well as the role of digital law in modern public life and issues of its development
Keywords: Law; digital law; blockchain